2015
DOI: 10.18632/oncotarget.4628
|View full text |Cite
|
Sign up to set email alerts
|

Stromal expression of ALDH1 in human breast carcinomas indicates reduced tumor progression

Abstract: Interactions between cancer cells and microenvironment are emerging issue in tumor progression. Aldehyde dehydrogenase 1 (ALDH1) is a recognized cancer stem cell marker but little is known about its role in intratumoral stroma. Therefore, we focused on ALDH1 expression in tumor-associated stroma of breast carcinomas (BrCa). In conclusion, ALDH1 expression in tumor-associated stromal cells indicates reduced BrCa progression, possibly via RA secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 48 publications
8
24
2
Order By: Relevance
“…Stromal positivity also indicated a longer time to BR and metastasis, and appeared even to be an independent predictor of good prognosis in the subgroup of d'Amico high risk patients. It is reasonable to conclude that ALDH1positive stromal cells might play a protective role in PCa, which is similar to the observation in breast cancer (2). ALDH1-positive stromal cells might hypothetically secrete retinoic acid and consequently in this way suppress tumor aggressiveness (2).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Stromal positivity also indicated a longer time to BR and metastasis, and appeared even to be an independent predictor of good prognosis in the subgroup of d'Amico high risk patients. It is reasonable to conclude that ALDH1positive stromal cells might play a protective role in PCa, which is similar to the observation in breast cancer (2). ALDH1-positive stromal cells might hypothetically secrete retinoic acid and consequently in this way suppress tumor aggressiveness (2).…”
Section: Discussionsupporting
confidence: 74%
“…It is reasonable to conclude that ALDH1positive stromal cells might play a protective role in PCa, which is similar to the observation in breast cancer (2). ALDH1-positive stromal cells might hypothetically secrete retinoic acid and consequently in this way suppress tumor aggressiveness (2). Retinoic acid is known to induce tumor cell differentiation and inhibit tumor cell proliferation and migration (7)(8)(9).…”
Section: Discussionsupporting
confidence: 69%
“…Another study 49 indicated that ALDH1A1 expression was associated with good outcomes in TNBC. Sj€ ostr€ om et al 50 reported that stromal ALDH1A1 was associated with better distant disease-free survival in BC. A possible explanation of the survival discrepancy in mRNA expression is that the stromal expression of ALDH1A1 was not completely removed during tissue processing in the process of RNA extraction.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 411 breast cancer patients treated at the University Medical Center Hamburg-Eppendorf during 1999 -2006 were included in this study as described (10 ). The variable clinicopathologic and molecular parameters were documented (see Table 1 in the Data Supplement that accompanies the online version of this article at http://www.…”
Section: Clinical Materialsmentioning
confidence: 99%